Pelatihan Penggunaan Peralatan Produksi yang Ramah Lingkungan Dalam Upaya Peningkatan Pendapatan Pada Bisnis Rumah Makan UMKM di Metro Atom Pasar Baru, PD Pasar Jaya DKI Jakarta - Tarmizi, Achmad; Meliantari, Dian; S, Shieto (Yayasan Daarul Huda Kruengmane, 2024)
Training on the Use of Environmentally Friendly Production Equipment in Efforts to Increase Income in MSME Restaurant Businesses at Metro Atom Pasar Baru, PD Pasar Jaya DKI Jakarta aims to provide training on the use of environmentally friendly production equipment to MSME restaurant business owners at Metro Atom Pasar Baru, PD Pasar Jaya DKI Jakarta. This activity focuses on efforts to increase income through implementing environmentally friendly practices in business operations. The training provided provides a better understanding of environmentally friendly production equipment and how to integrate it effectively in their daily activities. The adoption of environmentally friendly production equipment has resulted in cost efficiencies and reduced waste, which in turn increases business revenues. Thus, this training helps MSMEs increase their income while supporting environmental protection efforts. This research explores the impact of training in the use of environmentally friendly production equipment on the MSME restaurant business at Metro Atom Pasar Baru, PD Pasar Jaya DKI Jakarta. The results of the activity show that business owners are aware of the importance of environmental sustainability in their business operations but lack the knowledge and resources to implement it. Training provides a better understanding of environmentally friendly production equipment and its integration in daily activities. Implementation of environmentally friendly production equipment results in cost efficiencies and waste reduction, leading to increased business revenues. Thus, this training has the potential to help MSMEs increase their income while supporting environmental protection efforts.